Pengaruh Kemampuan, Motivasi Kerja dan Budaya Kerja terhadap Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Muara Teweh - Mukson Mukson; Hairudinor Hairudinor; Setio Utomo (Universitas Lambung Mangkurat, 2019)
The Research of Aim is to know how far the ability influence, work motivation and work culture to employee performances municipal waterwork in Muara Teweh. This Research is Descriftive Research, Data Analysis that using by multiple regression, by Simultaneously Hypothesis (F), Parcial Hypothesis (T), and Determination Koefesience.By the analysis result and hypothesis corresponding by thesis tittle of ability influence, works motivation, and works culture to employee performance municipal waterworks in Muara Teweh such as :The Ability (X1) significan influence to employee performance (Y) to municipal waterworks (PDAM) in Muara Teweh, motivation (X2) significan influence to employee performance (Y) to municipal waterworks in MuaraTeweh, works culture (X3) is not influence significan to employee performance (Y) to municipal waterworks Muara Teweh. The Ability (X1), work motivation (X2) and works culture (X3) that influence by simultancous (Y) to the employee (Y) to municipal waterworks in Muara Teweh.The municipal waterworks in Muara Teweh could evaluated and increasing works culture to reminds in this research of the municipal waterworks is so weak in Muara Teweh so order that is necessary to recovering and incresing. It’s can be proof by the result that decreased of works culture that employee performance will decrease, so that is not satisfying to serves to the society in Muara Teweh. Key Word : The Ability, Work Motivation, Works Culture, and employee performance.